Are cardiovascular and metabolic responses to field walking tests interchangeable and obesity-dependent?. Issue 18 (27th August 2016) - Di Thommazo-Luporini, Luciana; Carvalho, Lívia Pinheiro; Luporini, Rafael Luís; Trimer, Renata; Pantoni, Camila Bianca Falasco; Martinez, Adalberto Felipe; Catai, Aparecida Maria; Arena, Ross; Borghi-Silva, Audrey
Abstract: Purpose: To investigate if cardiovascular and metabolic responses to the six-minute walk test (6MWT) and incremental shuttle walking test (ISWT) are in agreement with cardiopulmonary exercise testing (CPX) and determine if both submaximal tests are interchangeable in obese and eutrophic individuals. Method: Observational and cross-sectional study included 51 obese women (ObG) and 21 controls (CG) (20–45 years old). Subjects underwent clinical evaluation, CPX, the 6MWT and ISWT. We applied Bland–Altman plots to assess agreement between walking tests and CPX. Correlation analysis assessed relationships between key variables. Results: There was an agreement between CPX and both the 6MWT [oxygen uptake (VO2 mL kg −1  min −1 ) = 6.9 (CI: 5.7–8.1), and heart rate (bpm) = 37.0 (CI: 33.3–40.7)] and ISWT [VO2 (mL kg −1  min −1 ) = 6.1 (CI: 4.9–7.3), and heart rate (bpm) = 36.2 (CI: 32.1–40.3)]. We found similar cardiovascular and metabolic responses to both tests in the ObG but not in the CG. Strong correlations were demonstrated between 6MWT and ISWT variables: VO2 ( r  = 0.70); dyspnoea ( r  = 0.80); and leg fatigue ( r  = 0.70). Conclusions: 6MWT and ISWT may both hold interchangeable clinical value when contrasted with CPX in obese women and may be a viable alternative in the clinical setting when resources and staffing are limited. Implications for Rehabilitation: Obesity is a worldwide epidemic, with high prevalence in women, and it is associated to impaired cardiorespiratory fitness and functional capacity as well as high mortality risk. Assessing oxygen uptake by means of cardiopulmonary exercise testing is the gold standard method for evaluating and stratifying cardiorespiratory fitness, however it is not ever applied due to costs and staffing. Walking field tests may be a cost-effective approach that provides valuable information regarding the functional capacity in agreement to metabolic and cardiovascular responses of cardiopulmonary exercise testing.